Sequence Variation In Cellulose Synthase (CesA) Gene From Shorea Parvifolia SSP. Parvifolia Mother Trees - Lau, Pauline (Universiti Malaysia Sarawak (UNIMAS), 2009)
Shona par.,ijolia ssp. parvijolia or locally known as meranti sarang punai, is the most sought after commercial valuable timber tree species. Genetic improvement programs based on phenotypic selection are inapplicable due to long generation time and poor juvenile-mature trait correlations of the species. In this study. targeted DNA sequence of cellulose synthase (CesA) was amplified by polymerase chain reaction (PeR) technique. DNA was extracted from five S. parvijolia ssp. parvijolia mother trees and subjected to PeR analysis using the designed primer set, SPPT3-F and SPPT3-R. The -800 bp CesA amplicons were subjected to BLASTn analysis to perform the sequence homology search through all known template sequence available in the NCB!. Sequence alignment was later carried out by CLC Free Workbench 4.0 for manual detection of SNPs. The consensus sequence of the five mother trees were then subjected to in silico restriction analysis. Two SNPs were detected in the exons and none in the introns of the -800 bp CesA amplicons. The exclusiveness of tbe restriction enzymes Earl and EcoRI obtained for SNPs at nucleotide 58 and 376 respectively could be usefuJ for genetic markers development.